[The lives of Mang Pandoy, Eden, and Vilma Santos [videorecording] - Lazaro, Cheche (The Probe Team, 1992)
Probe tells the changes in the lives of four Filipinos for whom 1992 was of some significance; Mang Pandoy, who is President Ramos symbol of the Filipino thirsting for economic upliftment; Victor, the streetkid Probe discovered four years ago; Emy, the bargirl left jobless and heartbroken with the closing of the U.S. bases; and Vilma Santos, the star for all seasons who is now Congressman Mrs. Ralph Recto.